تمثلات مدرسة بغداد للفن الحديث في رسوم ستار لقمان وحسن عبد علوان - hussen, ahmed (Basrah Arts Journal, 2025)
The Baghdadi School of Fine Arts is one of the most prominent artistic movements to emerge in Iraq during the twentieth century. It is distinguished by its efforts to integrate Arab cultural and civilizational heritage, particularly that of Baghdad, in light of social and political changes. The school inspired many artists, influenced by its Arab-Islamic style, which encompassed a profound vision of the Creator of the universe, the universe itself, and humanity. It is not surprising to note the influence of artistic heritage on artists Sattar Luqman and Hassan Abdul Alwan, through which they sought to create an expressive style that blended global artistic modernity with the spirit of Iraqi heritage, particularly the popular Baghdadi heritage. The researcher sought to study the worlds of both artists, seeking to find commonalities, differences, and similarities in an attempt to understand how the characteristics of the Baghdadi school were represented in their drawings. Based on this, the researcher was able to narrow down the research problem to the following question: What was the manner in which they dealt with drawing shapes, lines, and colors according to the aesthetics of the form, and intellectually in relation to previous or contemporary religious and intellectual ideas? The importance of the research lies in showing the representations of the Baghdadi school in the drawings of the artists Sattar Luqman and Hassan Abdul Alwan, and how they employ artistic elements according to a new vision, and how lines and colors operate on the surface of the Baghdadi painting technically, artistically and intellectually.